Central Giant Cell Lesion of the Maxilla. Case Study - Pakla, Paweł; Wojnar, Joanna; Lewandowski, Bogumił (Journal of Stomatology, 2015)
Introduction: Central Giant Cell Granuloma is a benign tumor detected mainly in the lateral segment of the mandible in children and adolescents. Although in most cases this lesion is benign, 20-40% of cases may be clinically aggressive and increase rapidly resulting in bone deformities, destruction of compact bone, soft tissue hyperplasia, bleeding from a tumor and dislocation or resorption of the teeth roots. Surgical treatment is the procedure of choice in this case. The range of the operation depends on a patient’s age, location, size of the lesion, clinical form of the tumor, the fact if it is a primary tumor or a relapse. The disease affects mostly young people, however, radical surgical treatment causes aesthetic and functional impairments that require a reconstruction and prosthetic rehabilitation. Therefore, alternative non-surgical treatment is administered more and more frequently. The Aim: of the paper is to present the case of a patient diagnosed with Central Giant Cell Granuloma (CGCL) whosetreatmentwasdividedintotwoparts:thefirst stage were intralesional injections with triamcinolone followed by a surgery. Conclusion: Based on clinical observations and follow up imaging the response of the organism to treatment was assessed as satisfactory. It was confirmed that while planning CGCL treatment, glucocorticoid injections can be considered as an alternative to a radical surgery. Tumor regression allowed to limit the extent of resection. Therefore, a surgical procedure can be performed which evokesless functional and aesthetic defects.